Perfumes Across Civilizations: A Brief Historical Study - AlZarooni, Hamda Mohamed Haidar; Alshamsi, Badryya Mohammed (Al-Adab Journal, 2022)
The civilizations of the ancient East have been known since the dawn of history plant aromatic scents, and they are the main source of all kinds of perfumes, including smoky, oily, fatty, resinous and watery, and its products include incense, musk, frankincense, myrrh, fragrant flowers, jasmine roses, and other first historical aromatic scents. Their importance continued throughout the history of civilizations humanity. Economic, social and cultural aspects of the civilizations of the ancient East, including Islamic civilization. Islamic civilization was considered one of the most important eras in forming the essence of the history of perfumes. The present research is divided into three sections and a conclusion in addition to a brief introduction to explain the term perfume as the first research explains perfumes in the civilizations of the ancient world in the East and dealing with perfume material from the religious aspect and its rituals. In addition, the topic of aromatic substances and perfumes for the purposes of adornment and beauty as in the ancient Egyptian and Mesopotamian civilizations, and the desire to control the nerves of economic life from the land and sea trade routes and areas that have been known since time immemorial for the precious aromatic riches that do not find another source for them, and the prosperity of the perfume trade markets and how the contribution of materials in controlling the movement of trade and the markets that existed as internal and external trade exchanges. The present study, among many other significant issues, proves the Islamic civilization’s interest in agriculture, including aromatic plants and flowers, the importance of perfume in Islamic civilization. And that it is one of the inherited elements as it became clear to some of the periods of Islamic history, and in this case the Abbasid caliphate. The study also will elaborate a numerous of literature in the field of perfume and its various types and usages.